2016
DOI: 10.1158/1078-0432.ccr-15-2364
|View full text |Cite
|
Sign up to set email alerts
|

Resident Memory T Cells as Surrogate Markers of the Efficacy of Cancer Vaccines

Abstract: Cancer vaccine boost via the cervicovaginal rather than the intramuscular route of immunization appears to be crucial to induce genital CD8+ T cells and tumor regression. This clinical activity is correlated with the ability of the mucosal boost to elicit resident memory T cells in the genital tract. Clin Cancer Res; 22(3); 530–2. ©2015 AACR. See related article by Sun et al., p. 657

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 15 publications
1
17
0
1
Order By: Relevance
“…Moreover, other immunostimulatory antibodies, such as anti-CD137, could also enhance the resident memory response38. In conclusion, our results support the notion that anti-tumour vaccination strategies should aim at the generation of both circulating and resident memory CD8 + T-cell subsets222339, which could synergize with checkpoint antibody therapy for improved cancer immunotherapy.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Moreover, other immunostimulatory antibodies, such as anti-CD137, could also enhance the resident memory response38. In conclusion, our results support the notion that anti-tumour vaccination strategies should aim at the generation of both circulating and resident memory CD8 + T-cell subsets222339, which could synergize with checkpoint antibody therapy for improved cancer immunotherapy.…”
Section: Discussionsupporting
confidence: 79%
“…Previous studies in human cancer show that the infiltration of tumours by T cells with a Trm cell-like phenotype correlates with improved overall survival in early stage non-small-cell lung carcinoma, pulmonary squamous cell carcinoma and high-grade serous epithelial ovarian cancer192021. In addition, recent results suggest that vaccination routes that promote generation of Trm cells could be more effective for anti-tumour response2223. These findings prompted us to analyse the relative contribution and plasticity of circulating memory CD8 + T cells and Trm cells in a model of anti-tumour vaccination.…”
mentioning
confidence: 99%
“…Indeed, mucosal, but not systemic, routes (intramuscular), generate a potent local T-cell response with a T RM phenotype, in parallel with a systemic response. For example, multiple studies, especially in an infectious context, have shown that tissue-specific vaccination is more effective at generating local immunity and T RM cells at barrier sites because it favors homing of immune cells to local sites [74]. In the same manner, heterologous prime-boost strategy with a cervico-vaginal boost enhances the establishment of specific CD8 + T cells expressing α 4 β 7 integrin in the genital tract compared to an intramuscular boost [67].…”
Section: Priming Of Trm Cells In Normal and Tumoral Tissuesmentioning
confidence: 99%
“…Dans des modèles précliniques, notre groupe a montré que, pour les tumeurs de localisation muqueuse, ces vaccins pourraient être amélio-rés en induisant une immunité pas seulement dans le sang des patients mais aussi au niveau du site tumoral muqueux [29]. Les voies muqueuses d'immunisation (intranasale, orale, intravaginale) pourraient représenter une approche pertinente pour l'obtention de réponses muqueuses antitumorales [30,31].…”
Section: Vaccins Antitumorauxunclassified